2018
DOI: 10.1002/slct.201703000
|View full text |Cite
|
Sign up to set email alerts
|

Fast Synthesis of Spherical Silica Aerogel Powders by Emulsion Polymerization from Water Glass

Abstract: In this study, a fast synthesis technique for silica aerogel powder was proposed that reduces the length of the tedious surface modification and solvent exchange processes. Spherical silica aerogel powder could be fabricated by an emulsion polymerization method from water glass and n-hexane. A stable water glass-in-hexane emulsion with a water glass to hexane ratio of 5:5 was fabricated using the surfactant, sorbitan monooleate (Span80). It was found that acetic acid and isopropanol catalysts for the hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In our previous study focusing on catalysts for hydrolysis and condensation of water glass, we proposed a novel fast synthesis technique for spherical silica aerogel powders with a narrow particle size distribution. This synthesis technique reduced the total processing time to less than 2 h [ 15 ]. However, silica aerogel powders using the aforementioned fast synthesis processes exhibit some drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study focusing on catalysts for hydrolysis and condensation of water glass, we proposed a novel fast synthesis technique for spherical silica aerogel powders with a narrow particle size distribution. This synthesis technique reduced the total processing time to less than 2 h [ 15 ]. However, silica aerogel powders using the aforementioned fast synthesis processes exhibit some drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Bhagat et al reported superhydrophobic silica aerogel powders with simultaneous surface modification, solvent exchange, and sodium ion removal from hydrogels [29]. Lee et al reported a fast synthesis technique for silica aerogel powders by an emulsion polymerization method using water glass, n-hexane, and a surfactant (Span80) [30]. Jiang et al prepared an amine-grafted silica aerogel microsphere by dropping the siliceous solution into a hot oil bath [31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because ions will partition preferentially into the aqueous phase, and the hydrophobic gel moves into the organic phase, this process can be carried out without any ion-exchange step prior to gelation. More recent variations of this approach to the synthesis of powders [27,[41][42][43][44][45] include gelation, hydrophobization, and solvent and ion-exchange in one single step. Hydrophobic silica aerogel powders are produced through the addition of an acid to a vigorously stirred two-phase mixture of waterglass and an organic phase (e.g.…”
Section: Introductionmentioning
confidence: 99%